2017
DOI: 10.1504/ijil.2017.10008282
|View full text |Cite
|
Sign up to set email alerts
|

Doing product development activities: the role of experience and ends-in-view

Abstract: Drawing on Deweyan pragmatism and the Science-Technology-Society approach, this ethnographic research aims at understanding the role of experience and ends-in-view when handling a product development activity. The research focuses on doings conceptualised as engineer-artefact reciprocity and contributes to practice-based learning and product development studies. The analysis demonstrates that past activities embodied in experience and materialised in artefacts and, likewise, future activities embodied in ends-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…When an individual(s) -scientist(s) and/or practitioner(s) is involved in doing TE, their individual logic of design enters into a kind of "means-end relation" [4]. The individuals' end-in-view (desired solution) differ [10]. By its nature, TE transcends boundaries -academic, professional, organisational and so on.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…When an individual(s) -scientist(s) and/or practitioner(s) is involved in doing TE, their individual logic of design enters into a kind of "means-end relation" [4]. The individuals' end-in-view (desired solution) differ [10]. By its nature, TE transcends boundaries -academic, professional, organisational and so on.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Our understanding of the basket of theories, the practice we study, and the current artefact is the fuel for our present actions and the telos for our present actions is to reach the desired situation. Thus, the desired situation that scientists and practitioners have in their views influences present action(s), but this desired situation may never be reached [10]. In other word, when doing the field test and evaluation it might be concluded that we did not successfully transform the problematic situation (S) into the desired situation (S*), but we arrived at situation (S´).…”
Section: Transdisciplinary Engineering Logicmentioning
confidence: 97%
See 3 more Smart Citations